ANALYSIS OF THE INFLUENCE OF LEADERSHIP STYLE, WORK STRESS AND COMPENSATION ON EMPLOYEE WORK PERFORMANCE AT PT. MULTIMAS NABATI ASAHAN MEDAN - Adrian Babtissay Simbolon (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to describe the influence of leadership style, work stress, and compensation on employee work performance at PT. Multimas Nabati Asahan Medan which lasted for 2 (two) months starting from April 2024 until May 2024. This research was using descriptive and quantitative methods. The respondents of this research are all employees at PT. Multimas Nabati Asahan Medan which has a total of 88 (eighty eight) employees. The instrument of this research is questionnaires to collect data from variables of leadership variables, variables of work stress, variables of compensation and variables of employee work performance. The technique of data analysis was using validity test, reliability test, descriptive analysis, normality test, multicolinearity test, heterocedacity test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test or t test, simultaneous test or F test, and calculation of coefficient determination. The results of descriptive analysis for variables of leadership style, variables of compensation and variables of employee work performance are in good category, while variables of work stress are in very not good category at PT. Multimas Nabati Asahan Medan. Based on the results of hypothesis testing partially, the variables of leadership style and compensation have a positive and significant influence on employee work performance at PT. Multimas Nabati Asahan Medan. While the variable of work stress has a negative and significant influence on employee work performance at PT. Multimas Nabati Asahan Medan. Silmutaneously, variables of leadership style, work stress and compensation have a positive and significant influence on employee work performance at PT. Multimas Nabati Asahan Medan. The contribution of leadership style, work stress and compensation to improve employee work performance is 0.773 or 77.3%., while the rest of 0.227 or 22.7% is influenced by other variables not investigated on this research such as motivation, discipline, communication, training, etc.